Indazole-Quinolone Hybrids as Anti-Virulence Agents against Pseudomonas aeruginosa - Marie Hanot; Marine Duplantier; Céline Dalle; Yani Ren; Sophie Da Nascimento; Jean-Paul Becker; Nicolas Taudon; Elodie Lohou; Pascal Sonnet (MDPI AG, 2024)
Antibiotic resistance is a critical public health issue. Among the multi-drug resistant microorganisms in question, Pseudomonas aeruginosa has been designated by the WHO as a priority threat. Its virulence is orchestrated through quorum sensing (QS). This sophisticated communication network relies on the release and perception of autoinducers acting as population density indicators. Therefore, the interest of a quorum silencing pharmacological approach has unfolded to quench bacterial pathogenicity without impairing growth. In this article, we reported the development of a family of indazole-quinolone hybrids as anti-virulence agents. These new biaromatic compounds were designed as potential specific QS quenchers against P. aeruginosa. Our transdisciplinary research methodology included their synthesis using palladocatalyzed cross-coupling reactions, as well as their in silico physicochemical and in vitro biological evaluation. The hit 7-chloro-2-indazolyl-4-quinolone Ie shows a promising anti-biofilm and anti-pyocyanin efficiency (35% inhibition at 25 µM and 35% inhibition at 100 µM, respectively) without an anti-pseudomonal bacteriostatic effect. It also demonstrated a moderate eukaryotic cytotoxicity. Its anti-QS properties have been investigated using metabolomic and molecular modelling studies.